Insulating material for electrochemical device
A PTFE composition with specific modifications is used to create an insulating member for electrochemical devices that maintains effective insulation at high temperatures, addressing the issue of short-circuits in devices like lithium-ion batteries.
Patent Information
- Application Number
- JP2024170721
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2024-09-30
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2044-09-30
AI Technical Summary
Existing insulating members for electrochemical devices fail to maintain effective insulation at high temperatures, leading to potential short-circuits in devices like lithium-ion batteries.
The use of a polytetrafluoroethylene (PTFE) composition that includes a homopolymer of tetrafluoroethylene or modified PTFE with 1.0% by mass or less of a modified monomer unit, specifically designed to maintain insulation even at high temperatures.
The proposed insulating member effectively maintains insulation at high temperatures, preventing short-circuits in electrochemical devices and ensuring reliable operation even when cells reach abnormally high temperatures.
Smart Images

Figure 2025060573000005 
Figure 2025060573000006 
Figure 2025060573000007
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an insulating member for an electrochemical device. [Background technology]
[0002] 2. Description of the Related Art It is known that resins such as perfluoroalkoxyalkane (PFA) are used as insulating members and sealing members for electrochemical devices such as lithium ion secondary batteries (see, for example, Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-174732 A [Patent Document 2] International Publication No. 2020 / 066050 [Patent Document 3] International Publication No. 2014 / 049645 Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present disclosure is to provide an insulating member for an electrochemical device that is capable of maintaining its insulating properties even at high temperatures. [Means for solving the problem]
[0005] The present disclosure (1) is an insulating member for electrochemical devices, comprising a polytetrafluoroethylene composition containing polytetrafluoroethylene, which is a homopolymer of tetrafluoroethylene or a modified polytetrafluoroethylene containing tetrafluoroethylene units and 1.0 mass% or less of modified monomer units.
[0006] The present disclosure (2) is the insulating member according to the present disclosure (1), in which the polytetrafluoroethylene composition has a heat of crystallization of 50 J / g or less.
[0007] The present disclosure (3) is the insulating member according to the present disclosure (1) or (2), wherein the polytetrafluoroethylene composition exhibits non-melt moldability.
[0008] The present disclosure (4) is an insulating member in any combination with any of the present disclosures (1) to (3), in which the polytetrafluoroethylene is the modified polytetrafluoroethylene.
[0009] The present disclosure (5) is an insulating member in any combination with any of the present disclosures (1) to (4), in which the modified monomer is perfluoro(propyl vinyl ether).
[0010] The present disclosure (6) is an insulating member in any combination with any of the present disclosures (1) to (5), in which the electrochemical device includes a non-aqueous electrolyte.
[0011] The present disclosure (7) is an insulating member that is an arbitrary combination with any of the present disclosures (1) to (6) which are gaskets.
[0012] The present disclosure (8) is an insulating member in any combination with any of the present disclosures (1) to (7), in which the content of modified monomer units in the modified polytetrafluoroethylene is 0.20 mass % or less based on the total polymerized units.
[0013] The present disclosure (9) is characterized in that the content of the polytetrafluoroethylene is 99.0% by mass or more relative to the polytetrafluoroethylene composition, The insulating member according to the present disclosure (8), wherein the content of the polytetrafluoroethylene composition is 99.0 mass % or more based on the insulating member.
[0014] The present disclosure (10) is the insulating member according to the present disclosure (9), having a melt flow rate of less than 0.10 g / 10 min.
[0015] The present disclosure (11) is an insulating member for electrochemical devices that exhibits non-melt formability.
[0016] The present disclosure (12) has a melt flow rate of less than 0.10 g / 10 min, The insulating member according to the present disclosure (11) contains polytetrafluoroethylene.
[0017] The present disclosure (13) is an insulating member in any combination with any of the present disclosures (1) to (12), in which the electrochemical device is a lithium ion battery or a sodium ion battery.
[0018] The present disclosure (14) is an insulating member having a heat of fusion of 50 J / g or more, which is any combination with any of the present disclosures (1) to (13). Effect of the Invention
[0019] According to the present disclosure, it is possible to provide an insulating member for an electrochemical device that is capable of maintaining its insulating properties even at high temperatures. [Brief description of the drawings]
[0020] [Figure 1] FIG. 2 is a schematic cross-sectional view showing an example of the configuration of a portion including an insulating member (gasket) of an electrochemical device. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an example of the configuration of a portion including an insulating member (gasket) of an electrochemical device. [Diagram 3] FIG. 2 is a schematic cross-sectional view showing an example of the configuration of a portion including an insulating member (gasket) of an electrochemical device. [Figure 4] FIG. 2 is a diagram showing a schematic diagram of a procedure for preparing a test assembly used for measuring insulation resistance. [Diagram 5] FIG. 2 is a diagram showing a schematic diagram of a procedure for preparing a test assembly used for measuring insulation resistance. [Figure 6] FIG. 1 is a schematic diagram of a test assembly used for measuring insulation resistance. [Figure 7] FIG. 2 is a diagram showing a schematic diagram of a step of measuring insulation resistance. [Figure 8] FIG. 2 is a schematic diagram of a permeation test fixture used in a water vapor permeation test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The present disclosure will now be described in detail.
[0022] The present disclosure provides an insulating member for electrochemical devices (hereinafter also referred to as insulating member (1) of the present disclosure) containing a PTFE composition containing PTFE, which is a homopolymer of tetrafluoroethylene (TFE) or modified polytetrafluoroethylene (PTFE) containing TFE units and 1.0 mass% or less of modified monomer units.
[0023] In this specification, unless otherwise specified, the insulating member (1) of the present disclosure and the insulating member (2) of the present disclosure described below are collectively referred to as the "insulating members of the present disclosure."
[0024] The insulating member (1) of the present disclosure contains a specific PTFE composition, and is thereby able to maintain its insulating properties even at high temperatures. In electrochemical devices that require a large output, such as a lithium-ion battery for power, a large number of cells are generally connected in parallel or series in close proximity to each other. In such a configuration, even if a nearby cell catches fire or the temperature of the cell becomes abnormally high (e.g., 400°C or higher), the insulating member (1) of the present disclosure can maintain good insulation properties and prevent short circuits of the cells and between the components of the cells.
[0025] The PTFE in the insulating member (1) of the present disclosure is a homopolymer of TFE or a modified PTFE. The modified PTFE is preferred because it has better insulation properties at high temperatures and also has low water vapor permeability.
[0026] The modified PTFE contains TFE units and 1.0% by mass or less of modified monomer units. The amount of TFE units may be 99.0% by mass or more. The modified PTFE may be composed of only TFE units and modified monomer units.
[0027] The modified PTFE preferably has a modified monomer unit content of 0.00001 to 1.0% by mass relative to the total polymerized units, in order to further improve the insulating properties at high temperatures and the low water vapor permeability. The lower limit of the modified monomer unit content is more preferably 0.0001% by mass, more preferably 0.001% by mass, even more preferably 0.005% by mass, and especially preferably 0.010% by mass. The upper limit of the modified monomer unit content is preferably 0.90% by mass, more preferably 0.80% by mass, more preferably 0.50% by mass, even more preferably 0.40% by mass, even more preferably 0.30% by mass, even more preferably 0.20% by mass, and especially preferably 0.10% by mass. In this specification, the modified monomer unit means a portion of the molecular structure of PTFE that is derived from a modified monomer.
[0028] The content of each of the above-mentioned polymer units can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.
[0029] The above-mentioned modified monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene [HFP], hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF], perhaloolefins such as chlorotrifluoroethylene [CTFE], perfluorovinyl ethers, perfluoroallyl ethers, (perfluoroalkyl)ethylenes, ethylenes, etc. The modified monomers used may be one type or multiple types.
[0030] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorovinyl ethers represented by the following general formula (A): CF2=CF-ORf 1 (A) (In the formula, Rf 1represents a perfluoro organic group. ) and the like. In this specification, the above-mentioned "perfluoro organic group" means an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The above-mentioned perfluoro organic group may have an ether oxygen.
[0031] The perfluorovinyl ether may be, for example, a compound represented by the general formula (A) in which Rf 1 and perfluoro(alkyl vinyl ether) [PAVE], which is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5.
[0032] Examples of the perfluoroalkyl group in the PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group.
[0033] The perfluorovinyl ether further includes, in the above general formula (A), Rf 1 is a perfluoro(alkoxyalkyl) group having 4 to 9 carbon atoms, Rf 1 is the following formula:
[0034] [ka]
[0035] (wherein m represents 0 or an integer of 1 to 4), Rf 1 is the following formula:
[0036] [ka]
[0037] (wherein n represents an integer of 1 to 4).
[0038] The (perfluoroalkyl)ethylene [PFAE] is not particularly limited, and examples thereof include (perfluorobutyl)ethylene [PFBE] and (perfluorohexyl)ethylene.
[0039] Examples of hydrogen-containing fluoroolefins include CH2=CF2, CFH=CH2, CFH=CF2, CH2=CFCF3, CH2=CHCF3, CHF=CHCF3 (E-form), and CHF=CHCF3 (Z-form).
[0040] The perfluoroallyl ether may, for example, be a compound represented by the general formula (B): CF2=CF-CF2-ORf 2 (B) (In the formula, Rf 2 represents a perfluoro organic group.
[0041] Above Rf 2 is preferably a perfluoroalkyl group having 1 to 10 carbon atoms or a perfluoroalkoxyalkyl group having 1 to 10 carbon atoms. The perfluoroallyl ether is preferably at least one selected from the group consisting of CF2=CF-CF2-O-CF3, CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9, more preferably at least one selected from the group consisting of CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9, and further preferably CF2=CF-CF2-O-CF2CF2CF3.
[0042] As the modified monomer, from the viewpoint of further improving the insulating properties at high temperatures and the low water vapor permeability, at least one selected from the group consisting of PAVE, PFAE, HFP and CTFE is preferable, at least one selected from the group consisting of PAVE and HFP is more preferable, PAVE is even more preferable, and perfluoro(propyl vinyl ether) [PPVE] is even more preferable.
[0043] The PTFE may have a core-shell structure. For example, the PTFE having a core-shell structure may be modified PTFE having a core of high molecular weight PTFE and a shell of lower molecular weight PTFE or modified PTFE in a particle. For example, the modified PTFE described in JP-T-2005-527652 may be used.
[0044] The PTFE may be PTFE obtained by emulsion polymerization or PTFE obtained by suspension polymerization. From the viewpoint of improving low water vapor permeability, PTFE obtained by emulsion polymerization is preferable, and unsintered PTFE (without a history of being heated to a temperature equal to or higher than the melting point) obtained by emulsion polymerization is more preferable.
[0045] In order to further improve the insulating properties at high temperatures, the PTFE composition preferably has an endothermic peak temperature of 333°C or higher, more preferably 335°C or higher, even more preferably 337°C or higher, and even more preferably 340°C or higher, and preferably 350°C or lower, and more preferably 346°C or lower. The endothermic peak temperature is a temperature corresponding to a minimum point in a heat of fusion curve obtained by performing differential scanning calorimetry (DSC) at a heating rate of 10° C. / min on a PTFE composition that has not been heated to a temperature of 300° C. or higher. When there are two or more minimum points in one melting peak, each of them is regarded as an endothermic peak temperature.
[0046] In order to further improve the insulating properties at high temperatures, the above-mentioned PTFE composition preferably has a melting point of 315°C or higher, more preferably 320°C or higher, even more preferably 323°C or higher, and even more preferably 325°C or higher, and preferably has a melting point of 335°C or lower, and more preferably 330°C or lower. The melting point is the temperature corresponding to the minimum point in the heat of fusion curve obtained by subjecting a PTFE composition that has been heated to a temperature of 300°C or higher to differential scanning calorimetry (DSC) at a heating rate of 10°C / min.
[0047] The PTFE composition may be a PTFE composition that is not completely sintered. A PTFE composition that is not completely sintered has a large heat of fusion and may take a long time to completely melt, so that it has an advantage that the temperature rise during heat generation can be delayed and it is possible to prevent the composition from reaching an abnormally high temperature in a short time.
[0048] The above-mentioned PTFE composition has a heat of fusion of preferably 27 J / g or more, more preferably 30 J / g or more, even more preferably 33 J / g or more, and particularly preferably 60 J / g or more, in that it can delay the temperature rise during heat generation and prevent the temperature from reaching an abnormally high temperature in a short period of time, and may have a heat of fusion of 90 J / g or less, or may have a heat of fusion of 80 J / g or less. The heat of fusion is a value measured using a differential scanning calorimeter (DSC).
[0049] In order to further improve the insulating properties at high temperatures, the PTFE composition preferably has a heat of crystallization of 50 J / g or less, more preferably 40 J / g or less, even more preferably 30 J / g or less, and even more preferably 25 J / g or less, and may be 10 J / g or more, or may be 15 J / g or more. The above heat of crystallization is a value measured using a differential scanning calorimeter (DSC).
[0050] In order to further improve the insulating properties at high temperatures, the PTFE composition has a thermal decomposition temperature of preferably 400° C. or higher, more preferably 430° C. or higher, and even more preferably 450° C. or higher. The thermal decomposition temperature may be 600° C. or lower, 550° C. or lower, or 520° C. or lower. The thermal decomposition temperature is the temperature at which the mass loss of the sample reaches 1% by mass when measured using a thermogravimetry and differential thermal analyzer (STA7200 manufactured by Hitachi High-Tech Science Corporation) at a heating rate of 10°C / min in an air atmosphere.
[0051] The PTFE composition has a melt viscosity of 1.0×10 at 380° C., which further improves the insulating properties at high temperatures. 7 It is preferable that the viscosity is 1.0×10 Pa s or more. 8 It is more preferable that the viscosity is 1.0×10 Pa s or more. 11 Pa s or less, and 5.0×10 10 It may be less than Pa·s. The melt viscosity is quantified using a melt viscoelasticity measuring device MCR302 (manufactured by Anton Paar Japan Co., Ltd.) A parallel plate with a diameter of 7 mm is used as the measuring tool, and the complex viscosity measured at a deformation rate of 0.3%, a sample thickness of 0.5 mm, a temperature of 380°C, and a frequency of 0.01 radians per second is defined as the melt viscosity.
[0052] In order to further improve the insulating properties at high temperatures, the above-mentioned PTFE composition preferably has a standard specific gravity (SSG) of 2.200 or less, more preferably 2.190 or less, even more preferably 2.180 or less, and even more preferably 2.175 or less, and may also be 2.130 or more, 2.140 or more, or 2.150 or more. The SSG is measured by a water displacement method according to ASTM D 792 using a sample molded according to ASTM D 4895 89.
[0053] The PTFE composition preferably has non-melt secondary processability. The non-melt secondary processability means a property that the melt flow rate cannot be measured at a temperature higher than the melting point in accordance with ASTM D-1238 and D-2116, in other words, a property that does not easily flow even in the melting temperature range.
[0054] The PTFE composition preferably exhibits non-melt moldability, which will be described later.
[0055] The PTFE composition may be a sintered PTFE composition or an unsintered PTFE composition. It may also be a PTFE composition that has a history of being heated to a temperature equal to or higher than the melting point, or a PTFE composition that has no history of being heated to a temperature equal to or higher than the melting point. PTFE compositions that have not been heated to temperatures above their melting point have the property of being stretchy and soft when processed into raw tape form. This means that they can easily conform to the shape of the part when wrapped around it, and can be easily attached to parts with simple shapes as well as parts with complex shapes, making it possible to provide insulation to the area around the part.
[0056] The PTFE composition may contain components other than the PTFE, but is preferably substantially composed of the PTFE. This allows the effects of the PTFE to be significantly exhibited. "Substantially composed of the PTFE" means that the PTFE content is 70% by mass or more relative to the PTFE composition. The content of the PTFE in the PTFE composition is preferably 90.0% by mass or more, more preferably 95.0% by mass or more, even more preferably 99.0% by mass or more, particularly preferably 99.9% by mass or more, and most preferably 99.95% by mass or more. It is also preferred that the PTFE composition consists solely of the PTFE.
[0057] The PTFE composition may contain a filler. The filler is preferably an insulating filler, and is not preferably a conductive filler. Examples of the filler include known insulating fillers such as aluminum oxide, silicon oxide, magnesium oxide, anhydrous magnesium carbonate, magnesium hydroxide, silicon oxide, silicon nitride, boron nitride, and aluminum nitride, and magnesium oxide, aluminum nitride, and boron nitride are preferred.
[0058] The insulating member (1) of the present disclosure may contain components other than the PTFE composition, but is preferably substantially made of the PTFE composition. This allows the effects of the PTFE composition to be significantly exhibited. "Substantially made of the PTFE composition" means that the content of the PTFE composition is 70% by mass or more relative to the insulating member. The content of the PTFE composition in the insulating member is preferably 90.0 mass% or more, more preferably 95.0 mass% or more, even more preferably 99.0 mass% or more, particularly preferably 99.9 mass% or more, and most preferably 99.95 mass% or more. It is also preferable that the insulating member (1) of the present disclosure consists of the above-mentioned PTFE composition.
[0059] The insulating member (1) of the present disclosure preferably exhibits non-melt formability, which will be described later.
[0060] The insulating member (1) of the present disclosure can be produced by forming a raw material composition containing raw material PTFE into a desired shape. The form of the raw material composition is not limited and may be a powder, a dispersion liquid, or the like, but is preferably a powder.
[0061] The above-mentioned raw material PTFE can be produced by emulsion polymerization or suspension polymerization.
[0062] The emulsion polymerization can be carried out by a known method. For example, in the presence of an anionic fluorine-containing surfactant and a polymerization initiator, the emulsion polymerization of monomers (TFE and optionally modified monomers) required for forming the PTFE is carried out in an aqueous medium to obtain an aqueous dispersion containing the PTFE particles (primary particles). In the emulsion polymerization, a chain transfer agent, a buffer, a pH adjuster, a stabilizing aid, a dispersion stabilizer, a radical scavenger, etc. may be used as necessary.
[0063] The obtained aqueous dispersion is coagulated to obtain a wet powder, and then the wet powder is dried to obtain a raw material PTFE powder. The coagulation and drying can be performed by a known method.
[0064] Suspension polymerization can be carried out, for example, by charging a monomer such as TFE, an aqueous medium, and other additives as necessary into a reactor, stirring the contents of the reactor, maintaining the reactor at a predetermined polymerization temperature, and then adding a predetermined amount of a polymerization initiator to start the polymerization reaction. After the start of the polymerization reaction, a monomer such as TFE, a polymerization initiator, a chain transfer agent, and the like may be additionally added depending on the purpose.
[0065] The suspension-polymerized particles thus obtained may be washed and then pulverized, or the suspension-polymerized particles thus obtained may be pulverized while being washed, to prepare pulverized particles.
[0066] The wet ground particles may be dehydrated and further dried for the purpose of removing moisture from the ground particles obtained by grinding.
[0067] After the suspension polymerized particles are pulverized, the pulverized particles obtained may be classified by a known method such as air classification.
[0068] The resulting pulverized particles may be granulated by a known granulation method.
[0069] By adjusting the polymerization and post-treatment conditions, the physical properties of the resulting PTFE can be adjusted. For example, in emulsion polymerization, the endothermic peak temperature can be increased, the standard specific gravity can be lowered, and the melt viscosity can be increased by reducing the amount of polymerization initiator used, reducing the amount of chain transfer agent used, and using a radical scavenger. In the post-treatment of emulsion polymerization, the decomposition temperature can be increased by setting the drying temperature at 150° C. or higher. In suspension polymerization, the endothermic peak temperature can be increased, the standard specific gravity can be lowered, and the melt viscosity can be increased by reducing the amount of polymerization initiator used, or by reducing the amount of chain transfer agent used, or preferably by not using any of the agent at all. In post-treatment, the decomposition temperature can be increased by washing the polymer and setting the drying temperature to 150°C or higher.
[0070] The method for molding the raw material composition is not particularly limited, and any known molding method can be used.
[0071] When using the powder obtained by emulsion polymerization, for example, the powder of the raw material composition and an extrusion aid can be mixed and paste extrusion molded. The extrusion aid can be removed by drying. It is also preferable to compress the powder of the raw material composition. The dispersion of the raw material composition may be applied to a substrate such as a glass cloth and dried. Firing may be performed as necessary.
[0072] When the powder obtained by suspension polymerization is used, for example, a molding method such as compression molding, ram extrusion molding, isostatic compression molding, etc., may be used. If necessary, calcination may be carried out. The PTFE molded body may be processed by machining such as cutting to produce a molded body having a desired shape. For example, a PTFE sheet can be obtained by cutting the PTFE molded body.
[0073] The present disclosure also provides an insulating member for electrochemical devices exhibiting non-melt formability (hereinafter also referred to as insulating member (2) of the present disclosure).
[0074] The insulating member (2) of the present disclosure exhibits non-melt moldability and can therefore maintain its insulating properties even at high temperatures. The insulating member (2) of the present disclosure can maintain good insulating properties even when the cells of an electrochemical device reach abnormally high temperatures (e.g., 400°C or higher), and can prevent short circuits in the cells and between the components of the cells.
[0075] In this specification, being non-melt moldable means that the melt flow rate (MFR) is less than 0.10 g / 10 min, preferably less than 0.01 g / 10 min. The MFR is a value obtained in accordance with ASTM D1238 using a melt indexer, as the mass (g / 10 min) of polymer flowing out per 10 min from a nozzle having an inner diameter of 2.095 mm and a length of 8 mm at 372° C. and a load of 5000 g (total load).
[0076] The insulating member (2) of the present disclosure may contain a resin exhibiting non-melt moldability (hereinafter also referred to as a non-melt moldable resin), a filler, etc. The non-melt moldable resin may be a fluororesin or a non-fluororesin.
[0077] The non-melt moldable resin has almost no fluidity at high temperatures, and therefore, in order to further improve the insulating properties, the thermal decomposition temperature is preferably 480° C. or higher, more preferably 485° C. or higher, even more preferably 490° C. or higher, even more preferably 492° C. or higher, and particularly preferably 495° C. or higher. Alternatively, the thermal decomposition temperature may be 600° C. or lower, 550° C. or lower, or 520° C. or lower. The thermal decomposition temperature is the temperature at which the mass loss of the sample reaches 1% by mass when measured using a thermogravimetry and differential thermal analyzer (STA7200 manufactured by Hitachi High-Tech Science Corporation) at a heating rate of 10°C / min in an air atmosphere.
[0078] It is also preferable that the non-melt-formable resin is crosslinked.
[0079] Examples of the non-melt moldable resin include PTFE, ultra-high molecular weight polyethylene, thermosetting resins, crosslinked resins, and the like. Among these, PTFE, ultra-high molecular weight polyethylene, phenolic resins, epoxy resins, melamine resins, urea resins, unsaturated polyester resins, alkyd resins, silicone resins, polyurethanes, thermosetting polyimides, and crosslinked polyethylenes are preferred, and PTFE and ultra-high molecular weight polyethylene are more preferred.
[0080] The PTFE may be the same as the PTFE in the insulating member (1) of the present disclosure.
[0081] The ultra-high molecular weight polyethylene has a weight average molecular weight of 1.0×10 6 More preferably, it is 2.0×10 6 More preferably, it is 7.0×10 or more. 7 It may be less than 7.0 x 10 6 It may be the following. The molecular weight of the ultra-high molecular weight polyethylene is measured by gel permeation chromatography (GPC) in terms of polystyrene.
[0082] Examples of commonly available ultra-high molecular weight polyethylene include Tiber UHMW-PE manufactured by Mitsubishi Chemical Advanced Materials Corporation and Hi-Zex Million manufactured by Mitsui Chemicals, Inc.
[0083] The filler is preferably an insulating filler, and is not preferably a conductive filler. Examples of the filler include known insulating fillers such as aluminum oxide, silicon oxide, magnesium oxide, anhydrous magnesium carbonate, magnesium hydroxide, silicon oxide, silicon nitride, boron nitride, and aluminum nitride, and magnesium oxide, aluminum nitride, and boron nitride are preferred.
[0084] The insulating member (2) of the present disclosure may contain components other than the non-melt moldable resin, but is preferably made substantially of the non-melt moldable resin. This allows the effects of the non-melt moldable resin to be significantly exhibited. "Made substantially of the non-melt moldable resin" means that the content of the non-melt moldable resin is 70% by mass or more relative to the insulating member. The content of the non-melt-formable resin in the insulating member is preferably 90.0 mass% or more, more preferably 95.0 mass% or more, even more preferably 99.0 mass% or more, particularly preferably 99.9 mass% or more, and most preferably 99.95 mass% or more. It is also preferable that the insulating member (2) of the present disclosure is made only of the non-melt moldable resin.
[0085] The insulating member (2) of the present disclosure can be produced by molding a raw material composition containing a raw material resin into a desired shape. The form of the raw material composition is not limited, and may be a powder, a dispersion liquid, or the like, but is preferably a powder. The molding method is also not limited, and in addition to the molding methods exemplified for the insulating member (1) of the present disclosure, known molding methods can be used.
[0086] The insulating member of the present disclosure is a member used for electrical insulation in an electrochemical device. The insulating member of the present disclosure may provide insulation between two or more conductive members of an electrochemical device, for example, between a positive electrode and a negative electrode, or between an electrode and another member (for example, an exterior such as a lid).
[0087] In order to further improve the insulating properties at high temperatures, the insulating member of the present disclosure preferably has an endothermic peak temperature of 333°C or higher, more preferably 335°C or higher, even more preferably 337°C or higher, and even more preferably 340°C or higher, and is preferably 350°C or lower, and more preferably 346°C or lower. The endothermic peak temperature is the temperature corresponding to the minimum point in the heat of fusion curve obtained by performing differential scanning calorimetry (DSC) at a heating rate of 10°C / min on an insulating material that has not been heated to a temperature of 300°C or higher. When there are two or more minimum points in one melting peak, each of them is regarded as an endothermic peak temperature.
[0088] In order to further improve the insulating properties at high temperatures, the insulating member of the present disclosure preferably has a melting point of 315°C or higher, more preferably 320°C or higher, even more preferably 323°C or higher, and even more preferably 325°C or higher, and preferably has a melting point of 335°C or lower, and more preferably 330°C or lower. The melting point is the temperature corresponding to the minimum point on the heat of fusion curve obtained by performing differential scanning calorimetry (DSC) at a heating rate of 10°C / min on an insulating material that has been heated to a temperature of 300°C or higher.
[0089] The insulating member of the present disclosure has a heat of fusion of preferably 27 J / g or more, more preferably 30 J / g or more, even more preferably 33 J / g or more, even more preferably 50 J / g or more, and particularly preferably 60 J / g or more, and may be 90 J / g or less, or may be 80 J / g or less, in that it can delay the rise in temperature when heat is generated and prevent the material from reaching an abnormally high temperature in a short period of time. The heat of fusion is a value measured using a differential scanning calorimeter (DSC).
[0090] In order to further improve the insulating properties at high temperatures, the insulating member of the present disclosure preferably has a heat of crystallization of 50 J / g or less, more preferably 40 J / g or less, even more preferably 30 J / g or less, and even more preferably 25 J / g or less, and may be 10 J / g or more, or may be 15 J / g or more. The above heat of crystallization is a value measured using a differential scanning calorimeter (DSC).
[0091] In order to further improve the insulating properties at high temperatures, the insulating member of the present disclosure has a pyrolysis temperature of preferably 400° C. or higher, more preferably 430° C. or higher, and even more preferably 450° C. or higher. Alternatively, the pyrolysis temperature may be 600° C. or lower, 550° C. or lower, or 520° C. or lower. The thermal decomposition temperature is the temperature at which the mass loss of the sample reaches 1% by mass when measured using a thermogravimetry and differential thermal analyzer (STA7200 manufactured by Hitachi High-Tech Science Corporation) at a heating rate of 10°C / min in an air atmosphere.
[0092] The insulating material of the present disclosure has a melt viscosity of 1.0×10 at 380° C., which further improves the insulating properties at high temperatures. 7 It is preferable that the viscosity is 1.0×10 Pa s or more.8 It is more preferable that the viscosity is 1.0×10 Pa s or more. 11 Pa s or less, and 5.0×10 10 It may be less than Pa·s. The melt viscosity is quantified using a melt viscoelasticity measuring device MCR302 (manufactured by Anton Paar Japan Co., Ltd.) A parallel plate with a diameter of 7 mm is used as the measuring tool, and the complex viscosity measured at a deformation rate of 0.3%, a sample thickness of 0.5 mm, a temperature of 380°C, and a frequency of 0.01 radians per second is defined as the melt viscosity.
[0093] In order to further improve the insulating properties at high temperatures, the insulating member of the present disclosure preferably has a standard specific gravity (SSG) of 2.200 or less, more preferably 2.190 or less, even more preferably 2.180 or less, and even more preferably 2.175 or less, and may be 2.130 or more, 2.140 or more, or 2.150 or more. The SSG is measured by a water displacement method according to ASTM D 792 using a sample molded according to ASTM D 4895 89.
[0094] The insulating member of the present disclosure preferably has non-melt secondary processability. The non-melt secondary processability means a property that the melt flow rate cannot be measured at a temperature higher than the melting point in accordance with ASTM D-1238 and D-2116, in other words, a property that does not easily flow even in the melting temperature range.
[0095] In order to further improve the insulating properties at high temperatures, the insulating member of the present disclosure preferably has an insulation resistance of 1 MΩ or more after heating at 450° C., more preferably 10 MΩ or more, and even more preferably 100 MΩ or more. The insulation resistance is measured by the method described in the examples below.
[0096] The insulating member of the present disclosure has good sealing properties even at high temperatures, and can therefore be suitably used as a sealing member. The sealing member is a member used to prevent leakage of liquid or gas or intrusion of liquid or gas from the outside. Examples of the sealing member include gaskets and packing, and among these, gaskets (insulating gaskets) are preferred.
[0097] The shape of the insulating member of the present disclosure is not particularly limited and may be, for example, an annular shape. Furthermore, the insulating member of the present disclosure may have a shape such as a circle, an oval, or a rectangle with rounded corners in a plan view and may have a through hole in the center.
[0098] The insulating member of the present disclosure may have a cylindrical portion and a flange portion extending radially from one opening of the cylindrical portion. An insulating member having such a structure can be suitably used, for example, for insulating an external terminal having a terminal head and an axial portion. In this embodiment, when the axial portion of the external terminal is arranged to face the inside of the electrochemical device (for example, when it faces the same direction as the external terminal 2 in FIG. 1 or FIG. 2 described later), the insulating member of the present disclosure is preferably arranged such that the opening of the cylindrical portion opposite the flange portion faces the inside of the electrochemical device. When the axial portion of the external terminal is arranged to face the outside of the electrochemical device (when it is upside down from the external terminal 2 in FIG. 1 or FIG. 2), the insulating member of the present disclosure is preferably arranged such that the opening of the cylindrical portion opposite the flange portion faces the outside of the electrochemical device.
[0099] A usage mode of an insulating member according to an embodiment of the present disclosure will be described with reference to the drawings.
[0100] 1, an electrochemical device 10 (for example, a sealed prismatic secondary battery) includes an outer can (not shown) and a lid 1. An electric element (not shown) such as a power generator is housed inside the outer can, and the opening of the outer can is hermetically sealed with the lid 1. The lid 1 is provided with an external terminal 2 (positive terminal or negative terminal), and externally generated power is supplied to an electric element via the external terminal 2 for storage, and also supplied to an external load.
[0101] In order to electrically insulate the external terminal 2 from the lid 1, an insulating member (gasket) 3 and an insulating plate 4 are provided on the lid 1. The insulating member 3 corresponds to the insulating member of the present disclosure. The external terminal 2 has a terminal head 21 having a rectangular parallelepiped block shape, and a cylindrical shaft portion 22. The shaft portion 22 protrudes from the lower surface of the terminal head 21 (on the inner side of the electrochemical device).
[0102] As shown in FIG. 1, the insulating member 3 has a cylindrical portion 31, a flange portion 32 that extends radially from one opening of the cylindrical portion 31, and a side wall portion 33 that rises from the periphery of the flange portion 32.
[0103] The cylindrical portion 31 is fitted onto the shaft portion 22 of the external terminal 2, and the inner peripheral surface of the cylindrical portion 31 abuts against the outer peripheral surface of the shaft portion 22. The cylindrical portion 31 is also inserted into the through hole of the lid 1, and the outer peripheral surface of the cylindrical portion 31 abuts against the inner peripheral surface of the through hole of the lid 1.
[0104] The flange portion 32 is sandwiched between the lid 1 and the external terminal 2 , with one contact surface of the flange portion 32 contacting the lower surface of the external terminal 2 and the other contact surface of the flange portion 32 contacting the surface of the lid 1 .
[0105] With the cylindrical portion 31 and the flange portion 32 of the insulating member 3 in a compressed state, the insulating member 3 comes into contact with the external terminal 2 and the lid 1, thereby ensuring the hermeticity of the electrochemical device.
[0106] The insulating member of the present disclosure may be used alone or in combination with other members. The insulating member of the present disclosure may be laminated with other members. The other members may be insulating members or sealing members.
[0107] It is preferable that the other components include a material different from the insulating component of the present disclosure, for example, a non-fluorine resin such as polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), or a fluorine resin other than PTFE such as tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymer (PFA).
[0108] Specific examples of the embodiment in which the insulating member of the present disclosure is used in combination with other members are shown in FIGS.
[0109] In Fig. 2, insulating member (gasket) 3 has member 3a, which contains PTFE and ensures insulation at high temperatures, and member 3b, which contains another material (e.g., PP) and ensures sealing properties under normal conditions other than high temperatures. Members 3a and 3b may be in contact with each other, or may be adjacent to each other but not in contact. Adjacent means that the members are not in contact with each other but are within a distance of 3 mm. The same effect can be obtained by swapping the materials and functions of members 3a and 3b.
[0110] In FIG. 3, insulating member (gasket) 3 has a laminated structure of member 3c which contains PTFE and ensures insulation at high temperatures, and member 3d which contains another material (e.g., PP) and ensures insulation under normal conditions other than high temperatures. The members 3c and 3d may be partially overlapped. A partially overlapped state means that when comparing the members 3c and 3d, there are parts where the members 3c and 3d do not overlap due to reasons such as the ends of the members not overlapping, the widths or depths being different, the positions being misaligned, or there being holes or gaps. By making member 3c smaller than member 3d, material costs can be reduced. By making member 3c larger than member 3d, insulation properties at high temperatures can be improved. Member 3c may have holes or gaps. In this case, material costs can be reduced. Insulation properties at high temperatures can be improved if there are no holes or gaps. Member 3c may be divided into multiple parts. In this case, assembly may be easier.
[0111] The following method can be exemplified as a method for realizing a structure in which the insulating member of the present disclosure and another member are laminated. (I) A molded article in which the insulating member of the present disclosure and other members are pre-laminated is produced, and the molded article is attached to an electrochemical device. (II) The insulating member of the present disclosure and another member, which are separate members, are attached to and fixed to an electrochemical device, thereby forming a laminate. (III) A portion of the surface of another member is coated with a material (such as PTFE) for forming the insulating member of the present disclosure, and then the member is attached to the electrochemical device.
[0112] As a specific method for coating in the above (III), the following method can be exemplified. (i) A dispersion (e.g., PTFE dispersion) containing the material of the insulating member of the present disclosure is applied to the surface of another member. This may then be dried. Further, this may then be sintered. (ii) Wrapping a sintered tape containing the insulating member material of the present disclosure (e.g., sintered PTFE tape) around the surface of another member. (iii) wrapping a fully unsintered or not sintered tape comprising the insulating member material of the present disclosure (e.g., fully unsintered or not sintered PTFE tape) around the surface of the other member; (iv) A tape that is not completely sintered or not sintered at all and that contains the material of the insulating member of the present disclosure (e.g., a PTFE tape that is not completely sintered or not sintered at all) is attached to the surface of another member. Attachment may be performed via an adhesive or glue.
[0113] The insulating member of the present disclosure is used in electrochemical devices such as batteries and capacitors. Examples of the battery include secondary batteries such as lithium ion batteries and sodium ion batteries. A sodium ion secondary battery is a secondary battery in which sodium ions in an electrolyte solution are responsible for electrical conduction. For example, sodium metal oxide can be used as the active material of the positive electrode. Examples of salts in the electrolyte include inorganic sodium salts such as NaPF6, NaBF4, NaClO4, and NaAsF6; and organic sodium salts such as NaCF3SO3, NaPF3(C2F5)3, NaN(CF3SO2)2, NaN(C2F5SO2)2, NaC(CF3SO2)3, and NaN(FSO2)2. Examples of materials for the negative electrode include hard carbon. The capacitor is not particularly limited, but is preferably an electrochemical capacitor. Examples of the electrochemical capacitor include an electric double layer capacitor, a hybrid capacitor, and a redox capacitor. Examples of the hybrid capacitor include a sodium ion capacitor, a lithium ion capacitor, and a magnesium ion capacitor. Among these, an electric double layer capacitor is particularly preferred.
[0114] INDUSTRIAL APPLICABILITY The insulating member of the present disclosure can be suitably used as an insulating member for batteries, and can be particularly suitably used as an insulating member for secondary batteries such as lithium ion batteries and sodium ion batteries.
[0115] The secondary battery may be a secondary battery that uses an electrolyte solution, or may be a solid-state secondary battery. In this specification, the solid-state secondary battery may be a secondary battery containing a solid electrolyte, and may be a semi-solid secondary battery containing a solid electrolyte and a liquid component as the electrolyte, or may be an all-solid-state secondary battery containing only a solid electrolyte as the electrolyte.
[0116] The insulating member of the present disclosure can be used in a state where it is in contact with an electrolyte included in an electrochemical device, i.e., it can have a contact surface with the electrolyte. Even when used in such a state, the insulating member of the present disclosure can maintain excellent insulating properties at high temperatures. The electrolyte referred to here includes not only the electrolyte itself but also substances derived from the electrolyte, and may be liquid, solid, or gas. The gas includes, for example, the volatilized electrolyte solution and gas generated by decomposition of the electrolyte solution during charging and discharging.
[0117] The electrochemical device according to the present disclosure preferably includes a nonaqueous electrolyte. The insulating member according to the present disclosure may be used in a state of contact with the nonaqueous electrolyte included in the electrochemical device, i.e., may have a liquid-contact surface with the nonaqueous electrolyte included in the electrochemical device.
[0118] The non-aqueous electrolyte may be prepared by dissolving a known electrolyte salt in a known organic solvent for dissolving electrolyte salts.
[0119] The organic solvent for dissolving the electrolyte salt is not particularly limited, and one or more of known hydrocarbon solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; and fluorine-based solvents such as fluoroethylene carbonate, fluoroethers, and fluorinated carbonates can be used.
[0120] Examples of electrolyte salts include LiClO4, LiAsF6, LiBF4, LiPF6, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, etc., and LiPF6, LiBF4, LiN(SO2CF3)2, LiN(SO2C2F5)2, or combinations of these are particularly preferred because of their good cycle characteristics.
[0121] The concentration of the electrolyte salt is preferably 0.8 mol / L or more, more preferably 1.0 mol / L or more. The upper limit depends on the organic solvent for dissolving the electrolyte salt, but is usually 1.5 mol / L.
[0122] The solid electrolyte used in the solid secondary battery may be a sulfide-based solid electrolyte or an oxide-based solid electrolyte. In particular, when a sulfide-based solid electrolyte is used, there is an advantage that the flexibility of the sheet is improved.
[0123] The sulfide-based solid electrolyte is not particularly limited, and examples thereof include Li2S-P2S5, Li2S-P2S3, Li2S-P2S3-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, LiI-Li2S-SiS2-P2S5, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li3PS4-Li4GeS4, Li 3.4 P 0.6 S 0.4 S4, Li 3.25 P 0.25 Ge 0.76 S4, Li 4-x Ge 1-x P x S4(x=0.6~0.8), Li 4+y Ge 1-y Ga y S4(y=0.2~0.3), LiPSCl, LiCl, Li 7-x-2y P.S. 6-x-y Cl x (0.8≦x≦1.7, 0 <y≦-0.25x+0.5)、Li 10 SnP2S 12 Any one selected from the above, or a mixture of two or more of them, can be used.
[0124] The sulfide-based solid electrolyte preferably contains lithium. The sulfide-based solid electrolyte containing lithium is used in a solid-state battery that uses lithium ions as a carrier, and is particularly preferred in terms of electrochemical devices having a high energy density.
[0125] The oxide-based solid electrolyte is preferably a compound that contains an oxygen atom (O), has the ionic conductivity of a metal belonging to Group 1 or 2 of the periodic table, and has electronic insulation properties.
[0126] Specific examples of compounds include Li xa La ya TiO3 [xa=0.3~0.7, ya=0.3~0.7] (LLT), Li xb La yb Zr zb M bb mb O nb (M bb is at least one of the elements Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn, where xb satisfies 5≦xb≦10, yb satisfies 1≦yb≦4, zb satisfies 1≦zb≦4, mb satisfies 0≦mb≦2, and nb satisfies 5≦nb≦20. ), Li xc B yc M cc zc O nc (M cc is at least one element selected from C, S, Al, Si, Ga, Ge, In, and Sn, where xc satisfies 0≦xc≦5, yc satisfies 0≦yc≦1, zc satisfies 0≦zc≦1, and nc satisfies 0≦nc≦6. ), Li xd (Al,Ga) yd (Ti,Ge) zd S ad P md O nd (where 1≦xd≦3, 0≦yd≦2, 0≦zd≦2, 0≦ad≦2, 1≦md≦7, 3≦nd≦15), Li (3-2xe) M ee xe D ee O(xe is a number between 0 and 0.1, and M ee represents a divalent metal atom. ee represents a halogen atom or a combination of two or more halogen atoms. xf S yf O zf (1≦xf≦5, 0 <yf≦3、1≦zf≦10)、Li xg S yg O zg (1≦xg≦3, 0 <yg≦2、1≦zg≦10)、Li3BO3-Li2SO4、Li2O-B2O3-P2O5、Li2O-SiO2、Li6BaLa2Ta2O 12 , LiPO(4-3 / 2w) N w (w is w<1), Li with LISICON (Lithium super ionic conductor) type crystal structure 3.5 Zinc 0.25 GeO4, La with perovskite crystal structure 0.51 Li 0.34 TiO 2.94 , La 0.55 Li 0.35 TiO3, LiTi2P3O with NASICON (sodium super ionic conductor) type crystal structure 12 , Li 1+xh+yh (Al,Ga) xh (Ti,Ge) 2-xh S yh P 3-yh O 12 (where 0≦xh≦1, 0≦yh≦1), Li7La3Zr2O with a garnet-type crystal structure 12 (LLZ) and others. Ceramic materials in which elements have been substituted for LLZ are also known. For example, Li 6.24 La3Zr2Al 0.24 O 11.98 , Li 6.25 Al 0.25 La3Zr2O 12 and Li substituted with Ta 6.6 La3Zr 1.6 Ta 0.4 O 12 , Li substituted with Nb 6.75 La3Zr 1.75 Nb 0.25 O 12 Other examples include LLZ-based ceramic materials in which at least one of Mg (magnesium) and A (A is at least one element selected from the group consisting of Ca (calcium), Sr (strontium), and Ba (barium)) is substituted for LLZ. Phosphorus compounds containing Li, P, and O are also desirable. For example, lithium phosphate (Li3PO4), LiPON, LiPOD, in which part of the oxygen in lithium phosphate is substituted with nitrogen, etc. 1 (D 1is at least one selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt, Au, etc. In addition, LiA 1 ON(A 1 is at least one selected from Si, B, Ge, Al, C, Ga, etc. Specific examples include Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2 and Li2O-Al2O3-SiO2-P2O5-TiO2.
[0127] The oxide-based solid electrolyte preferably contains lithium. The oxide-based solid electrolyte containing lithium is used in a solid-state battery that uses lithium ions as a carrier, and is particularly preferred in terms of electrochemical devices having a high energy density.
[0128] The oxide-based solid electrolyte is preferably an oxide having a crystalline structure. Oxides having a crystalline structure are particularly preferred in terms of good Li-ion conductivity. Examples of oxides having a crystalline structure include perovskite-type (La 0.51 Li 0.34 TiO 2.94 etc.), NASICON type (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), garnet type (Li7La3Zr2O 12 (LLZ), etc. Among these, the garnet type is preferred.
[0129] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims. EXAMPLES
[0130] The present disclosure will now be described in more detail with reference to examples, but the present disclosure is not limited to these examples.
[0131] Various physical properties were measured by the following methods.
[0132] <Modified monomer content> The PPVE content in PTFE was determined by press-molding the sample to produce a thin-film disk, measuring the infrared absorbance of the thin-film disk using FT-IR, and determining the PPVE content at 995 cm -1 Absorbance at / 935cm -1 The absorbance ratio was calculated by multiplying the absorbance ratio at The PPVE content in PFA was measured using an NMR analyzer (eg, AVANCE300 high temperature probe manufactured by Bruker Biospin).
[0133] <Standard specific gravity (SSG)> Using samples molded in accordance with ASTM D4895 89, the measurement was performed by the water displacement method in accordance with ASTM D 792.
[0134] <Heat of fusion> The obtained sheet was cut, and about 3 mg was weighed and stored in a dedicated aluminum pan. Using X-DSC7000 (Hitachi High-Tech Science Co., Ltd.), the temperature was raised to the melting peak temperature +40°C at a rate of 10°C / min under a nitrogen atmosphere, and the heat of fusion was measured. The heat of fusion was calculated by drawing a line from the melting peak temperature -40°C to the melting peak temperature +20°C on the obtained DSC chart, and the area enclosed by the curve including the peak and the line.
[0135] <Heat of crystallization> The obtained sheet was cut, and about 3 mg was weighed and stored in a dedicated aluminum pan. Using X-DSC7000 (Hitachi High-Tech Science Co., Ltd.), the temperature was raised to the crystallization peak temperature +40°C at a rate of 10°C / min under a nitrogen atmosphere, and after holding for 1 minute, the temperature was lowered to the crystallization peak temperature -60°C at a rate of 10°C / min to measure the heat of crystallization at the crystallization point. The value of the heat of crystallization was obtained by drawing a line from the crystallization peak temperature -30°C to +25°C on the obtained DSC chart, and calculating the area enclosed by the curve including the peak and the line.
[0136] <Melt viscosity> The melt viscosity was quantified using a melt viscoelasticity measuring device MCR302 (manufactured by Anton Paar Japan Co., Ltd.). A parallel plate with a diameter of 7 mm was used as the measuring tool, and the complex viscosity measured at a deformation rate of 0.3%, a sample thickness of 0.5 mm, a temperature of 380°C, and a frequency of 0.01 radians per second was taken as the melt viscosity. If the viscosity is too low or the sample polymer gasifies due to thermal decomposition, the viscosity should be set to 100 Pa s or less.
[0137] <Melt moldability (MFR)> According to ASTM D1238, the mass of polymer flowing out of a nozzle with an inner diameter of 2.095 mm and a length of 8 mm per 10 minutes was measured at 372°C and a load of 5000 g (total load) using a melt indexer. MFR of 0.10 g / 10 min or more indicates melt moldability, and MFR of less than 0.10 g / 10 min does not indicate melt moldability (non-melt moldability). Note that MFR is less than 0.10 g / 10 min when the fluidity is too low to measure. If the fluidity is too high or the sample polymer gasifies due to thermal decomposition, the MFR is set to 100 g / 10 min or more.
[0138] <Insulation resistance> Using the obtained sheet, a test piece 11 (a = 3.5 mm, b = 0.2 mm, c = d = 30 mm in Fig. 4(a)) was made, which was a square sheet of 30 mm × 30 mm × 0.2 mm thick with a hole of φ3.5 mm in the center, as shown in Fig. 4(a). As shown in FIG. 4(b), the test piece 11 and the washer 12 (e=6.5 mm, f=18 mm, g=1 mm in FIG. 4(b)) were stacked and fixed so that the centers of the holes of the test piece 11 and the washer 12 were aligned. As shown in Figure 5(a), the hole of the test piece 11 was enlarged with a taper punch 13 (in Figure 5(a), h = 1 mm, i = 8 mm, j = 40 mm) to form a cylindrical sleeve portion whose outer peripheral surface abuts against the inner peripheral surface of the hole of the washer 12. As shown in FIG. 5(b), the shaft of a pin 14 (in FIG. 5(b), k=6 mm, l=12 mm, m=6 mm, n=8 mm) having a disk-shaped base and a cylindrical shaft was inserted into the sleeve portion to obtain a test assembly 100 shown in FIG. 6. As shown in FIG. 7(a), a tubular jig 101 was placed over the washer 12 of the test assembly 100, and the test assembly 100 was placed in an electric furnace with a load of 5 kg being applied via the tubular jig 101 in the direction of the arrow shown in FIG. 7(b). The specimen was heated in an electric furnace to an initial temperature of 250°C, and then heated to a holding temperature of 450°C at a heating rate of 10°C / min. The specimen was heat-treated for 10 minutes at the holding temperature, and then cooled to room temperature. After cooling, the load was removed, and the resistance between the washer 12 and the pin 14 was measured with an insulation measuring device (Digital Megaohm Tester 3454, manufactured by Hioki E.E. Corporation) at an applied voltage of 250V. If the insulation resistance was more than 100 MΩ, it was determined that there was insulation after heating at 450°C, and if it was less than 10 Ω, it was determined that there was no insulation after heating at 450°C. The insulation was also evaluated in the same manner when the holding temperature was 350° C. If the insulation resistance was more than 100 MΩ, it was determined that there was insulation after heating at 350° C., and if it was less than 10 Ω, it was determined that there was no insulation after heating at 350° C.
[0139] <Water vapor permeability test> As shown in Fig. 8, 2 g of water 42 was placed in an aluminum alloy cup 41. A gasket 47 was placed between the cup 41 and a gasket compression jig 43, and a lid 44 was fastened with a bolt 45 to compress the gasket 47. A spacer 46 was placed between the lid 44 and the cup 41, and the compression rate of the gasket 47 was adjusted to 37.5% or 58%. The compression ratio was calculated from the following formula. (Gasket compression rate (%))={1-(distance of the gap (gasket placement portion) between cup 41 and gasket compression jig 43) / (height of gasket before compression)}×100 The mass of the permeation test jig 40 thus obtained was measured. The permeation test jig 40 was placed in an electric furnace at 80°C, and after leaving it for 1000 hours, it was taken out and left at room temperature for 2 hours, after which the mass was measured. The water vapor permeability coefficient was calculated using the following formula. This operation was repeated three times to calculate the average value of the water vapor permeability coefficient. The average value is shown in Table 2. Water vapor permeability coefficient (g / 1000hr) = (mass of permeability test fixture before heating) - (mass of permeability test fixture after heating)
[0140] Example 1 PTFE powder (TFE homopolymer obtained by suspension polymerization, SSG=2.159) was compression molded under the condition of 30 MPa pressure and held for 5 minutes, and then heated to 365°C at a rate of 50°C / min in an electric furnace, and heat-treated at 365°C for 5.5 hours, and then cooled to room temperature to obtain a molded body with a diameter of 50 mm. The obtained molded body was cut to obtain PTFE sheet A with a thickness of 0.2 mm. PTFE sheet A showed non-melt moldability. Various physical properties were measured by the above-mentioned methods using PTFE sheet A. The results are shown in Table 1. From the obtained φ50 mm molded body, a circular gasket A with a square cross section of inner diameter φ14.3 mm × outer diameter φ17.7 mm × height 1.6 mm was obtained. Gasket A showed non-melt processability. A water vapor permeation test was carried out using gasket A to measure the water vapor permeation coefficient. The results are shown in Table 2.
[0141] Example 2 A lubricant (product name: Isopar G (registered trademark), manufactured by Exxon) was mixed with PTFE powder (TFE homopolymer obtained by emulsion polymerization, SSG=2.172), and the mixture was paste-extruded using a sheet-shaped extrusion die, and the lubricant was removed by heat treatment at 230°C for 30 minutes to obtain a 0.2 mm-thick PTFE sheet B. The PTFE sheet B exhibited non-melt moldability. Various physical properties were measured by the above-mentioned methods using PTFE sheet B. The results are shown in Table 1. Similarly, the PTFE powder was mixed with a lubricant, and the mixture was paste-extruded using a mold RR100 described in ASTM D4895, and the lubricant was removed by heat treatment at 30°C for 30 minutes to obtain a PTFE round bar E having a diameter of about 2.5 mm. The PTFE round bar exhibited non-melt moldability. The PTFE round bar was bent into a circle with an inner diameter of 16 mm, and the ends of the strands were overlapped by 3 mm to form a gasket shape, to obtain Gasket B. Gasket B showed non-melt processability. A water vapor permeation test was carried out using gasket B to measure the water vapor permeation coefficient. The results are shown in Table 2.
[0142] Example 3 A PTFE sheet C having a thickness of 0.2 mm was obtained in the same manner as in Example 1, except that a PTFE powder (PPVE-modified PTFE obtained by suspension polymerization (TFE / PPVE=99.89 / 0.11% by mass), SSG=2.175) was used instead of the PTFE powder in Example 1. The PTFE sheet C showed non-melt moldability. Various physical properties were measured by the above-mentioned methods using PTFE sheet C. The results are shown in Table 1.
[0143] Comparative Example 1 PFA pellets (TFE / PPVE=96.1 / 3.9% by mass, MFR=15.3 g / 10 min) were melted at 370° C. for 20 minutes using a hot plate press, and then cooled with water while being pressurized at 1 MPa to obtain a PFA sheet with a thickness of 0.2 mm. The PFA sheet showed melt moldability. The PFA sheet was used to measure various physical properties using the methods described above. The results are shown in Table 1.
[0144] Comparative Example 2 A PTFE sheet D having a thickness of 0.2 mm was obtained in the same manner as in Comparative Example 1, except that PTFE powder (TFE homopolymer, MFR=22 g / 10 min) was used instead of the PFA pellets in Comparative Example 1. The PTFE sheet D exhibited melt moldability. Various physical properties were measured by the above-mentioned methods using PTFE sheet D. The results are shown in Table 1.
[0145] Comparative Example 3 A 0.2 mm thick PP sheet was produced in the same manner as in Comparative Example 1, except that polypropylene (PP) (product name: Prime Polypro F227, manufactured by Prime Polymer Co., Ltd.) was used instead of the PFA pellets used in Comparative Example 1, and the hot plate press temperature was 280°C instead of 370°C. The various physical properties of the PP sheet were measured by the methods described above. The results are shown in Table 1. Similarly, PP was heated to above its melting point to produce a sheet, from which was obtained an annular gasket C having a square cross section with an inner diameter of φ14.3 mm × outer diameter of φ17.7 mm × height of 1.6 mm. A water vapor permeation test was carried out using gasket C to measure the water vapor permeation coefficient. The results are shown in Table 2.
[0146] Comparative Example 4 A 0.2 mm thick PBT sheet was prepared in the same manner as in Comparative Example 1, except that polybutylene terephthalate (PBT) (product name: PBT Natural Color Unfilled, manufactured by Kureha Extron Co., Ltd.) was used instead of the PFA pellets in Comparative Example 1, and the hot plate press temperature was 280°C instead of 370°C. The PBT sheet was used to measure various physical properties using the methods described above. The results are shown in Table 1. Similarly, PBT was heated to above its melting point to produce a sheet, from which was obtained a circular gasket D having a square cross section with an inner diameter of φ14.3 mm, an outer diameter of φ17.7 mm, and a height of 1.6 mm. A water vapor permeability test was carried out using gasket D to measure the water vapor permeability coefficient. The results are shown in Table 2.
[0147] [Table 1] [Table 2]
[0148] The PTFE sheets (PTFE compositions) produced in the examples were suitable for use as insulating members for electrochemical devices. [Explanation of symbols]
[0149] 10: Electrochemical devices 1: Lid 2: External terminal 21:Terminal head 22: Shaft 3: Insulating material (gasket) 31: Cylindrical part 32: Flange part 33: Side wall 4: Insulating plate 11: Test piece 12: Washer 13: Taper punch 14: Pin 100: Test assembly 101: Tubular jig 40: Transmission test fixture 41: Cup 42:Water 43: Gasket compression tool 44: Lid 45: Bolt 46: Spacer 47: Gasket
Claims
1. An insulating member for electrochemical devices comprising a polytetrafluoroethylene composition containing polytetrafluoroethylene, which is a homopolymer of tetrafluoroethylene or a modified polytetrafluoroethylene containing tetrafluoroethylene units and 1.0 mass % or less of modified monomer units.
2. 2. The insulating member according to claim 1, wherein the polytetrafluoroethylene composition has a heat of crystallization of 50 J / g or less.
3. 3. The insulating member according to claim 1, wherein the polytetrafluoroethylene composition exhibits non-melt moldability.
4. 3. The insulating member according to claim 1, wherein the polytetrafluoroethylene is a modified polytetrafluoroethylene.
5. 3. The insulating member according to claim 1, wherein the modified monomer is perfluoro(propyl vinyl ether).
6. The insulating member according to claim 1 or 2, wherein the electrochemical device comprises a non-aqueous electrolyte.
7. 3. The insulating member according to claim 1, which is a gasket.
8. 3. The insulating member according to claim 1, wherein the content of the modified monomer unit in the modified polytetrafluoroethylene is 0.20 mass % or less based on the total polymer units.
9. The content of the polytetrafluoroethylene is 99.0% by mass or more based on the polytetrafluoroethylene composition, 9. The insulating member according to claim 8, wherein the content of the polytetrafluoroethylene composition is 99.0 mass % or more based on the insulating member.
10. 10. The insulating member according to claim 9, having a melt flow rate of less than 0.10 g / 10 min.
11. An insulating material for electrochemical devices that exhibits non-melt formability.
12. A melt flow rate of less than 0.10 g / 10 min; 12. The insulating member of claim 11 comprising polytetrafluoroethylene.
13. 13. The insulating member according to claim 1, 2, 11 or 12, wherein the electrochemical device is a lithium ion battery or a sodium ion battery.
14. 13. The insulating material according to claim 1, 2, 11 or 12, having a heat of fusion of 50 J / g or more.
Citation Information
Patent Citations
Fluorine-based resin porous body
JP2015221861A
Layered body and extrusion-molded article
JP2021075053A
Fluororesin film
WO2018142933A1
Power storage device
JP2017174732A
Gasket for secondary cell, and secondary cell
WO2014049645A1